Investigating the Effects of Nutrition, Concentration, and Motor Development on Physical Education Outcomes in Elementary School Students - Khairul Afriadi; Wilda Welis; Eri Barlian; Hastria Effendi (JETL (Journal of Education, Teaching and Learning), 2025)
This study examines the low learning outcomes of students at SD Negeri 004 Tanjungpinang Barat, which are allegedly influenced by nutritional status, concentration, and self-control skills. This quantitative study uses a correlational design with an ex-post-facto method. The research sample was 100 students selected through purposive sampling technique. Nutritional status data were obtained from height and weight measurements, concentration was measured by the grid concentration test, self-control skills by the TGMD-2 subtest, and learning outcomes were obtained from school data. The data were analyzed using path analysis. The results showed that there was a direct relationship between nutritional status, concentration, and self-control skills on student learning outcomes. The contribution of nutritional status to learning outcomes was 16.66%, concentration was 21.48%, and self-control skills were 19.75%. In addition, there is an indirect relationship between nutritional status and concentration on learning outcomes through self-control skills. Overall, nutritional status, concentration, and self-control skills contribute significantly to student learning outcomes by 35.04%.